Temperature dependent physicochemical characteristics, antibacterial and cytotoxic potential of iron quantum cluster templated hydroxyapatites. Issue 3 (1st February 2022) - Hashemi, Naimeh; Vaezi, Zahra; Masoumi, Saeed; Mohammadi, Sanam Sadeghi; Mahdavian, Reza; Sedghi, Mosslim; Redl, Heinz; Banerjee, Asmita; Weidinger, Adelheid; Naderi-Manesh, Hossein
Abstract: Design and development of novel nanobiomaterials with multifunctional properties hold the promise of new therapeutic strategies to improve the current clinical research in the field of tissue engineering and regenerative medicine. Here, we have successfully synthesized novel autofluorescent hydroxyapatite (HAP) using a template-assisted assembly process followed by a hydrothermal method. Iron quantum cluster (FeQC) were applied as an ideal template for obtaining fluorescent HAP nanorod-assembled microspheres under different hydrothermal temperatures. We evaluated the changes in physicochemical properties, cell viability, and antibacterial activity of HAP microstructures at 120 °C, 150 °C, and 180 °C reaction temperatures. The obtained HAP samples showed an increase in size, a decrease in surface area, and also, a change in the emission wavelength range when the synthesis temperature increases. The cytotoxicity assay results of human amniotic membrane epithelial cells and C2C12 cell line revealed that the HAP with the higher specific surface area show more interaction with cells which lead to higher cytotoxicity effect. The produced HAPs displayed an inhibition zone for Escherichia coli and Staphylococcus aureus bacteria. Therefore, they showed synergistic antibacterial activity against both Gram-negative and Gram-positive bacteria. Our data clearly revealed that the presented biocompatible, multicolor, and highly stable fluorescent HAPs with considerable antibacterial and antioxidant activity have great potential for imaging applications as well as the prevention of implant-associated infections. Graphical abstract: Image 1 Highlights: A novel fluorescent Hydroxyapatites (HAP) were fabricated at different hydrothermal temperatures. The fluorescent HAP samples were synthesized using iron quantum cluster as a template. The produced HAPs exhibited multicolor fluorescence emission. The Fluorescent HAP samples exhibited cell-type dependence cytotoxic activity. The synthesized HAPs showed potent antibacterial effect against E.coli and S.aureus bacteria.